Patienter sur les places et foncer dans les rues. Quand les coursiers occupent l’espace public - Émilie Aunis; Hélène Stevens (Images du Travail, Travail des Images)
Based on a survey mixing observations and interviews, this article studies the working practices of couriers in the public space. These practices, polarized between an unproductive time of waiting—not devoid of forms of rationalization of the activity and during which sociabilities between peers are engaged—and a remunerative delivery time—which gives rise to optimization strategies involving physical resistance, risk-taking and logics of moderation. Between waiting in the squares and rushing through the streets, these workers are caught up in various tensions, one of which is the central one between the visibility of their presence in the public space and the invisibility of their work.